The Representation of South Korean Culture and History in the Moon Lovers: Scarlet Heart Ryeo TV Series - Puji Lestari; Lambok Hermanto Sihombing (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This research explores the film's portrayal of South Korea. This research focuses on the scene in Moon Lovers that depicts South Korean history and culture. The qualitative approach is used to analyze the data in this study. The dataset was taken from the scenes on Moon Lovers, korea.net, and any other journal articles. The theories applied include Mise en Scene approach, Stuart Hall's representation theory and cultural theory. As a result, the outcome of this study reveals a detailed and recognized picture of South Korean history and culture.